Evaluation of Mangosteen Peel Extract Dosage on the Percentage of Male Guppy Fish (Peocilia reticulata) - Yusnita Alisa; Misbahkhul Ikhwan; Amru Ahmad Musyaffa; Ida Nur Safitri; Tegar Kurizai; Azis Rizal Gunawan (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2025)
This study aims to determine the best dose of mangosteen peel extract as a natural ingredient to increase the percentage of male sex in guppy larvae Poecilia reticulata aged less than 5 days. Mangosteen peel extract was prepared through maceration with 70% ethanol, then applied by immersion method for 2 hours at various doses of 1000; 1100; 1200; 1300; and 1400 ppm along with one control without treatment, using a Completely Randomized Design with three replications. Parameters observed included the percentage of males-females, survival rate, and water quality (temperature and pH). The results showed that a dose of 1.4 ppm produced the highest male percentage of 57% and provided high survival, while a dose of 1 ppm produced the lowest male percentage. Xanthone compounds in mangosteen peel are thought to act as aromatase inhibitors that reduce estrogen formation thereby directing gonadal differentiation towards males. Thus, mangosteen peel extract at a dose of 1.4 ppm is effective as a natural masculinizing agent to increase the proportion of male guppies without reducing survival.